The earliest modern Anglo-Saxon grammar: Sir Henry Spelman, Abraham Wheelock and William Retchford. (24th July 2017) - Lucas, Peter J.
Abstract: The first scholars interested in Anglo-Saxon had to learn it by direct contact with original sources. Work on a dictionary preceded that on a grammar, notably through the efforts of John Joscelyn, Archbishop Parker's Latin Secretary. Like Parker, Sir Henry Spelman (1563/4–1641) found that many of his sources for early English history were in Anglo-Saxon. Consequently he encouraged the study of Old English by establishing a Lectureship in Anglo-Saxon at Cambridge University and worked closely with its first (and only) holder, Abraham Wheelock. Together with Wheelock's pupil, William Retchford, and possibly drawing on some earlier work by Joscelyn (since lost), these scholars attempted to formulate the rudiments of Anglo-Saxon grammar. This pioneering work, basically a parts-of-speech grammar, survives in three versions, two of them incomplete. In this article I discuss the contents and methodology used and present for the first time an edited text of the first modern Old English grammar. It was a remarkable achievement.